Study of Profile on Juvenile criminals in Chennai (Indian Journal of Forensic Medicine & Toxicology, 2020)
Juvenile delinquency is a serious offence and it is detrimental for the social order in any country .There isa trend of increase in juvenile crimes world-over, with more and more involvement of the youth in violentcrimes. Chennai shows similar trends of increasing rate of violent crimes committed by the juveniles. It is avery serious concern for the district and solutions to end the problem need to be sought very carefully. Indianlegal system and judiciary has responded to these trends and has brought some amendments in the lawspertaining to juvenile justice in India [1]. This paper aims at looking at the causes of juvenile delinquencyand explanations in Chennai for the year 2016. The analysis of statistical data available at the CBCIDoffice crime branch indicates increasing involvement of the juveniles in heinous crimes. Observation homes,Shelter homes have been started by the government for the sake of such offenders then also the rate iscontinuously increasing day by day. For delinquent juvenile we can say that Prevention is better than curejuveniles should be protected from going to the wrong path.